Targeting BCL2 With BH3 Mimetics: Basic Science and Clinical Application of Venetoclax in Chronic Lymphocytic Leukemia and Related B Cell Malignancies - Roberts, AW (Clin Pharmacol Ther, 2016)
The intracellular protein B‐cell‐lymphoma‐2 (BCL2) has been considered an attractive target for cancer therapy since the discovery of its function as a major promoter of cell survival (an anti‐apoptotic) in the late 1980s. However, the challenges of targeting a protein‐protein interaction delayed the discovery of fit‐for‐purpose molecules until the mid‐2000s. Since then, a series of high affinity small organic molecules that inhibits the interaction of BCL2 with the apoptotic machinery, the so‐called BH3‐mimetics, have been developed. Venetoclax (formerly ABT‐199) is the first to achieve US Food and Drug Administration approval, with an indication for treatment of patients with previously treated chronic lymphocytic leukemia (CLL) bearing deletion of the long arm of chromosome 17. Here, we review key aspects of the science underpinning the clinical application of BCL2 inhibitors and explore both our current knowledge and unresolved questions about its clinical utility, both in CLL and in other B‐cell malignancies that highly express BCL2.